Musical decolonisation: the reception of Pablo Casals in Japan and the Sinophone world - Min-Erh Wang (2023)

(untitled)
This thesis, ‘Musical decolonisation: The reception of Pablo Casals in Japan and the Sinophone world,’ discusses the reception of Western art music in Japan, Taiwan, China, and Hong Kong through the lens of colonialism, the Cold War, and capitalism with a case study on the Spanish cellist and humanitarian Pablo Casals (1876-1973).